Fabrication of Cu Wiring Touch Sensor via Laser Sintering of Cu Nano/Microparticle Paste on 3D‐Printed Substrate. Issue 1 (9th October 2020) - Ahn, Hyeon-Sik; Oh, Ae-Sun; Kim, Dong-Hwan; Choi, Yoonseuk; Kim, Kyung-Hyun; Bae, Hyun-Cheol
Abstract : This study investigates the applications of 3D printing technology in the wiring process used in the field of electronic packaging. A Cu wiring process is developed to replace the expensive Ag‐based alternative primarily used in commercial 3D electronic circuit printing as per industry standards. The substrates needed for our experiments are developed using a 3D printer assembled prior to the research, through which poly‐ether‐ether‐ketone (PEEK) proves to be a high‐strength, high heat‐resistance material capable of undergoing the packaging process. The Cu wiring process is performed via laser sintering in ambient condition using a Cu micro/nanoparticle paste. Adopting this method minimizes the cost and duration of the process without relying on inert atmosphere generation. The optimum laser sintering condition for the Cu paste is found to be two consecutive scans at 20 W. Energy dispersive X‐ray spectroscopy (EDS) measurements show that the oxidation of the surface is about 1.35%, and further oxidation is prevented through epoxy molding. The touch sensor by Cu wiring module operate optimally even a month after its manufacture. 3D printing technology proves to be capable of replacing the wiring process used for electronic packaging. Abstract : Cu wiring is proposed as a replacement for the expensive conventional Ag wiring and successfully applied in a 3D printing technology. Laser sintering is adopted using Cu micro/nanoparticle paste that can effectively fill voids without cracking. This process prevents the oxidation of Cu and reduces the process duration and cost by not relying on inert atmosphere conditions.